Comparison of Mack Chain-Ladder and Bootstrap Methods for Claim Reserve Estimation under IFRS 17 in Lampung General Insurance - Tiara Yulita; Putri Isnaini Cahyaning Baiti; Dila Tirta Julianty; Ayu Sofia; Dwi Mahrani; M. Naufal Athaatmaja (JTAM (Jurnal Teori dan Aplikasi Matematika), 2026)
Claim  reserves are funds set aside by insurance companies to pay for reported claims (RBNS) as well as claims that have not yet been reported (IBNR), and they are crucial because they directly affect the financial health of the company. In 2024, there were customer complaints in Lampung regarding delays in claim payments by general and life insurance companies. Therefore, this study uses claim data from general insurance companies in Lampung for the period 2013–2024. The novelty of this study lies in comparing the Mack Chain Ladder analytical method and the Bootstrap simulation method for estimating claim reserves within the IFRS 17 framework using regional insurance data from Lampung, which has not been widely explored in previous studies. This study aims to estimate claim reserves and estimate the Liability for Incurred Claims (LIC),The objective of this study is to compare claim reserve values using an analytical approach (Mack Chain-Ladder) and a simulation approach (Bootstrap), implemented in accordance with the International Financial Reporting Standard (IFRS) 17. The IFRS 17 components to be calculated include the Liability for Incurred Claims (LIC) , Best Estimate Liability (BEL), and Risk Adjustment (RA) under IFRS 17. . Accurate estimation of claim reserves and the implementation of IFRS 17 play a vital role in ensuring the sustainability of insurance companies. The Mack Chain-Ladder (MCL) method is used to obtain equations for the expected value and variance of future claims as well as the prediction error rate. Meanwhile, the Bootstrap method generates numerous simulated claim datasets that reflect various possible scenarios. The advantage of the simulation approach is its ability to provide a full predictive distribution, which can be used to estimate the risk adjustment under IFRS 17. The empirical results show that the estimated claim reserve using the Mack Chain-Ladder (MCL) method is 234,740,644, while the Bootstrap method with 5.000 simulations produces a reserve range ofIn addition, this study also discusses methods for calculating capital requirements based on Value at Risk and for estimating risk adjustment using risk measures applied to the simulated distribution of claim liabilities over the contract period. 233,158,004-236,320,156. These results provide empirical insights into claim reserve estimation and support the implementation of IFRS 17 in regional insurance companies by calculating the BEL, RA, and LIC values, whose results are based on the claim reserve calculation .